GE_GERICHTE P/4618/2016 vom 20. November 2018 - GE Cour de justice (2018)
IN DUBIO PRO REO ; MAÎTRISE DU VÉHICULE ; PRINCIPE DE LA CONFIANCE(RÈGLE DE LA CIRCULATION) | LCR.26.al1; CEDH.6.al2; LCR.31.al1; OCR.3.al1